Fractional Free Volume Dependence of Neutron-IrradiatedPolystyrene (PS) Measured by Positron Method - Al-Bayati, A. (Iraqi Journal of Science, 2025)
The fractional free volume (Fh) in polystyrene (PS) as a function of neutron-irradiation dose has been measured, using positron annihilation lifetime (PAL) method. The results show that Fh values decreased with increasing n-irradiation dose up to a total dose of 501.03x 10-2 Gy.A percentage reduction of 2.14 in Fh values is noticed after the initial n-dose corresponding to a percentage reduction of 42.14/Gy. The total n-dose induces a percentage reduction of 7.26, corresponding to a percentage reduction of 1.45 per Gy. These results indicate that cross -linking is the predominant process induced by n-irradiation.The results suggest that n-irradiation induces structure changes in PS, causing cross-linking in PS chains, whereas the presence of oxygen during irradiation causes retardness of cross-linking yield, which consequently affects the values of the above mentioned parameter with respect to their values in case the irrad-iation is performed in vacuum.